Penggunaan Kata Serapan Istilah Asing dalam Teks Nonfiksi Buku Siswa Kelas VI Sekolah Dasar - Nindya Nurdianasari; Nala Ni’matul Mardiyah; Hari Satrijono; Fajar Surya Hutama; Linda Purnamasari Rukmana (Universitas Negeri Makassar, 2022)
The purpose of this research is to describe the forms of loanwords of foreign terms and the process of their absorption in the non-fiction texts for 6th grade students’ books on the theme of Bumiku, sub-theme of earth, sun, and moon, and their use as student teaching materials. The type of research used descriptive qualitative. Data in this research obtained through documentation in the form loanwords of foreign terms in 5 non-fiction text titles. Data analysis performed by reducing, presenting, and verifying data. Based on the result of the research, it was found that the forms of foreign words adopted, Arabian adapted word, English adaptations, Sanskrit adaptations, Dutch adaptations, and other language adaptations. The absorption process includes adoption and adaptation. The utilization of the result of this analysis used as additional teaching material for 6th grade.